Exploring the triad of mathematical engagement: Perceived abilities, interests, and teacher-student dynamics - Zhumabay, Nurman; Balta, Nuri; Zhadrayeva, Larissa; Yilmaz, Satilmis; Nadelson, Louis S. (Journal on Mathematics Education, 2024)
This study investigates the relationships between students' perceptions, interests, and engagement in mathematics within the cultural framework of K-12 education in Kazakhstan. A diverse sample of K-12 students representing various grade levels and community settings was included in the research. The analysis proceeded in three distinct phases: first, a Confirmatory Factor Analysis (CFA) was conducted to evaluate the reliability of the instrument; second, a Structural Equation Modeling (SEM) approach was applied to examine relationships between variables and assess the overall model fit; and finally, descriptive and inferential statistical methods were employed. Students perceived mathematical abilities and interests were identified as significant predictors of their attitudes toward mathematics teachers, as revealed through SEM. Due to the nature of the data, nonparametric tests were utilized to explore group differences. The findings indicated a consistent pattern of negative student perceptions regarding their mathematical abilities and interests, juxtaposed with positive attitudes toward their mathematics teachers. These positive attitudes were more closely associated with students' personal rapport with teachers rather than their instructional effectiveness. Further analyses examined variations in perceptions across different grade levels and community settings, revealing the influence of contextual factors. Notably, no significant gender differences were observed, challenging existing literature on gender disparities in education. The study underscores the importance of adopting holistic educational strategies that account for cultural contexts and promote teacher-student solid relationships.